Food safety in the 21st century : public health perspective - Gupta, Rajul Kumar; Dudeja, Puja; Minhas, Amarjeet Singh; ScienceDirect eBooks (London : Academic Press, 2017)
Food Safety in the 21st Century: Public Health Perspective is an important reference for anyone currently working in the food industry or those entering the industry. It provides realistic, practical, and very usable information about key aspects of food safety, while also systematically approaching the matter of foodborne illness by addressing the intricacies of both prevention and control. This book discusses ways to assess risk and to employ epidemiological methods to improve food safety. In addition, it also describes the regulatory context that shapes food safety activities at the local, national, and international levels and looks forward to the future of food safety.
Foodborne diseases: disease burden / S. V. Bhaskar -- Foodborne infectious diseases / R. K. Gupta -- Outbreak investigation of foodborne illnesses / A. Khera -- Surveillance of foodborne illnesses / A. Khera -- Role of risk analysis and risk communicaiton in food safety management / D. P. Attrey -- An ayurvedic perspective on food safety / J. Kumar -- Food safety in modern society: changing trends of food production and consumption / P. Dudeja, A. Singh -- Food toxicology: past, present, and the future (the Indian perspective) / S. P. Singh, S. Kaur, D. Singh -- Toxicological profile of Indian foods: ensuring food safety in India / S. P. Singh, S. Kaur, D. Singh -- Detection of food adulterants/contaminants / D. P. Attrey -- Recent advances in detection of food adulteration / D. Banerjee, S. Chowdhary, S. Chakraborty, R. Bhattacharyya -- Role of public health food safety laboratories in detection of adulterants/contaminants / D. P. Attrey -- Food-safety issues related to plant foods at farms / P. Dudeja, A. Singh -- Food safety from farm-to-fork: food safety issues related to animal foods at farm / P. Dudeja, A. Singh -- Food safety from farm-to-fork: food safety issues related to processing / P. Dudeja, A. Singh -- Food safety issues in production of foods of animal origin and from farm to plate / D. P. Attrey -- Safe storage and cooking practices for foods of animal origin in home kitchen before consumption / D. P. Attrey -- Role of government authorities in food safety / P. Dudeja, A. Singh -- Local governing bodies / R. K. Gupta -- Role of food business operators in food safety / P. Dudeja, A. Singh -- Food handlers / P. Dudeja, A. Singh -- Consumers / P. Dudeja, R. K. Gupta -- Public health professionals and food safety / R. K. Gupta -- Role of veterinary experts in food safety / D. P. Attrey -- Researchers and food safety / R. K. Gupta, P. Dudeja -- Role of hotel management and catering technology institutes in ensuring food safety / I. Kaur -- Food safety in large organized eating establishments / P. Dudeja, A. Singh -- Design and construction of eating establishments for ensuring food safety / P. K. Ahuja -- Safe cooking practices and food safety in home kitchen and eating establishment / P. Dudeja, A. Singh -- Food safety in schools, canteens, hostel messes, mid-day meal scheme, ICDS / R. K. Gupta -- Food safety issues related to street vendors / S. Malhotra -- Food safety during travel / S. Kathirvel -- Food safety during fairs and festivals / G. Ghose, I. Saha -- Food safety during disasters / R. K. Gupta -- Relevant food safety regulations and policies / D. P. Attrey -- Food safety policies in agriculture and food security with traceability / D. P. Attrey -- Food safety in international food trade: imports and exports / D. P. Attrey -- Regulation of advertisement for food products in India: advertisement for food products / S. Bajaj -- Nutritional labeling / P. Dudeja, R. K. Gupta -- Nutraceuticals / P. Dudeja, R. K. Gupta -- Regulatory requirements for labeling, health and nutritional claim / D. P. Attrey -- Genetically modified (GM) foods: the food security dilemma / J. Dutta -- Organic farming: is it a solution to safe food / M. Bansal -- Safety and quality of frozen foods / D. P. Attrey -- Ready to eat meals / R. K. Gupta, P. Dudeja -- Food packaging / R. K. Gupta, P. Dudeja -- Information technology (IT) in food safety / R. K. Gupta.
Includes bibliographical references and index.
Description based on print version record.
Elsevier
Keywords: Food adulteration and inspection; Food industry and trade -- Safety measures; Food industry and trade -- Quality control; TECHNOLOGY & ENGINEERING -- Food Science; BUSINESS & ECONOMICS -- Infrastructure; Food adulteration and inspection; Food industry and trade -- Quality control; Food industry and trade -- Safety measures; Electronic books